Addressing Inequities in Access to Health Products through the Use of Social Marketing, Community Mobilization, and Local Entrepreneurs in Rural Western Kenya. (28th May 2012) - Harris, Julie R.; Patel, Minal K.; Juliao, Patricia; Suchdev, Parminder S.; Ruth, Laird J.; Were, Vincent; Ochieng, Cliff; Faith, Sitnah Hamidah; Kola, Steven; Otieno, Ronald; Sadumah, Ibrahim; Obure, Alfredo; et al.
Abstract : While social marketing can increase uptake of health products in developing countries, providing equitable access is challenging. We conducted a 2-year evaluation of uptake of WaterGuard, insecticide-treated bednets (ITNs), and micronutrient Sprinkles in Western Kenya. Sixty villages were randomly assigned to intervention and comparison groups. Following a baseline survey (BL), a multifaceted intervention comprising social marketing of these products, home visits by product vendors from a local women's group (Safe Water and AIDS Project, or SWAP), product promotions, and modeling of water treatment and safe storage in was implemented in intervention villages. Comparison villages received only social marketing of WaterGuard and ITNs. We surveyed again at one year (FU1), implemented the intervention in comparison villages, and surveyed again at two years (FU2). At BL, <3% of households had been visited by a SWAP vendor. At FU1, more intervention than comparison households had been visited by a SWAP vendor (39% versus 9%, P < 0.0001 ), and purchased WaterGuard (14% versus 2%, P < 0.0001 ), Sprinkles (36% versus 6%, P < 0.0001 ), or ITNs (3% versus 1%, P < 0.04 ) from that vendor. During FU2, 47% and 41% of original intervention and comparison households, respectively, reported ever receiving a SWAP vendor visit (P = 0.16 ); >90% those reported ever purchasing a product from the vendor. WaterGuard (P = 0.02 ) and ITNs (P = 0.005 ) were purchased less frequently by lower-SES than higher-SES households; Sprinkles, the least expensive product, was purchased equally across all quintiles.